2021
DOI: 10.21203/rs.3.rs-227796/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Passive Immunity Trial for Our Nation (PassITON): study protocol for a randomized placebo-control clinical trial evaluating COVID-19 convalescent plasma in hospitalized adults

Abstract: Background: Convalescent plasma is being used widely as a treatment for coronavirus disease 2019 (COVID-19). However, the clinical efficacy of COVID-19 convalescent plasma is unclear. Methods: The Passive Immunity Trial for Our Nation (PassITON), is a multicenter, placebo-controlled, blinded, randomized clinical trial being conducted in the United States to provide high-quality evidence on the efficacy of COVID-19 convalescent plasma as a treatment for adults hospitalized with symptomatic disease. Adults hospi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Although over 100,000 patients were infused under the EAP, the absence of a matched comparison cohort limits the use of this data to assess the effectiveness of CP (8,17). Furthermore, randomized control trials (RCTs) struggled with enrollment, design and cohort selection, nimbleness, and aligning site selection with local outbreaks, which resulted in underpowered and/or inconsistent conclusions on the efficacy of convalescent plasma (6,16,(18)(19)(20)(21)(22)(23)(24). Most matched studies and RCTs around the globe have shown a trend of CP providing survival benefit, but all had relatively small cohorts except the RECOVERY trial (N=11,558), which failed to show benefit with CP (20,25).…”
Section: Introductionmentioning
confidence: 99%
“…Although over 100,000 patients were infused under the EAP, the absence of a matched comparison cohort limits the use of this data to assess the effectiveness of CP (8,17). Furthermore, randomized control trials (RCTs) struggled with enrollment, design and cohort selection, nimbleness, and aligning site selection with local outbreaks, which resulted in underpowered and/or inconsistent conclusions on the efficacy of convalescent plasma (6,16,(18)(19)(20)(21)(22)(23)(24). Most matched studies and RCTs around the globe have shown a trend of CP providing survival benefit, but all had relatively small cohorts except the RECOVERY trial (N=11,558), which failed to show benefit with CP (20,25).…”
Section: Introductionmentioning
confidence: 99%
“…Need for mechanical ventilation 4. SOFA scale ≥3 at 72 h after randomization or an increase in 2 points or more from the basal level 2.44%, 14 and 28 days Low titer: Vircell SL (Spain) test, correlates to ≥1:320 S-RBD IgG 309 , 312 NCT04362176 3 2021 USA Completed 1000 Inpatients with or without supplemental oxygen COVID-19 7-point Ordinal Clinical Progression Outcomes Scale (ranging from 1 (not hospitalized with resumption of normal activities) to 7 (death)) Not defined, 14 and 28 days 50% neutralization titer >1:50 (neutralizing antibodies) are selected for transfusion in the trial, Abbott™ ARCHITECT™ platform and the RBD Luminex assay 313 NCT04323800 2 2021 USA Completed 180 Outpatients 1. Efficacy of treatment at day 28 2.…”
Section: Convalescent Plasma Therapy For Covid-19mentioning
confidence: 99%